2014
DOI: 10.5897/ajb11.3687
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of chitinolytic bacterial isolates to control anthracnose of cocoa leaf caused by Colletotrichum gloeosporioides

Abstract: Colletotrichum spp. are causal agents of anthracnose in many plant species. Biological control of Colletotrichum spp. utilizing bacterial isolates and fungi has been reported. However, chitinolytic bacterial isolate utilization to control anthracnose of cocoa leaf has not seemingly been studied yet. In this study, we used chitinolytic bacterial isolates to reduce anthracnose severity and incidence caused by Colletotrichum gloeosporioides. Identification of the chitinolytic isolates was conducted for their morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…In addition to D. tulliensis , F. proliferatum , F. solani and N. clavispora , several studies have reported the occurrence of other species as plant pathogens associated with T. cacao . For example, Colletotrichum gloeosporioides , Colletotrichum tropicale , Colletotrichum siamense , D. pseudomangiferae , Lasiodiplodia pseudotheobromae , Lasiodiplodia theobromae , Neofusicoccum parvum , Nigrospora sphaerica , Phytophthora palmivora and Phytophthora megakarya (Akrofi et al., 2015; Asare et al., 2021; Huda‐Shakirah et al., 2022; Huda‐Shakirah & Mohd, 2023; Puig et al., 2021; Serrato‐Diaz et al., 2020, 2022; Suryanto et al., 2014; Villanueva et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to D. tulliensis , F. proliferatum , F. solani and N. clavispora , several studies have reported the occurrence of other species as plant pathogens associated with T. cacao . For example, Colletotrichum gloeosporioides , Colletotrichum tropicale , Colletotrichum siamense , D. pseudomangiferae , Lasiodiplodia pseudotheobromae , Lasiodiplodia theobromae , Neofusicoccum parvum , Nigrospora sphaerica , Phytophthora palmivora and Phytophthora megakarya (Akrofi et al., 2015; Asare et al., 2021; Huda‐Shakirah et al., 2022; Huda‐Shakirah & Mohd, 2023; Puig et al., 2021; Serrato‐Diaz et al., 2020, 2022; Suryanto et al., 2014; Villanueva et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In (Akrofi et al, 2015;Asare et al, 2021;Huda-Shakirah et al, 2022;Huda-Shakirah & Mohd, 2023;Puig et al, 2021;Serrato-Diaz et al, 2020Suryanto et al, 2014;Villanueva et al, 2023).…”
Section: Pathogenicity Testunclassified
“…( 28 32 ), and Colletotrichum spp. ( 33 ). Despite some success, application of exogenous biocontrol agents may only provide short-term disease suppression [e.g., 50% protection at 5 weeks, with no measurable effect after 7 weeks ( 17 )].…”
Section: Introductionmentioning
confidence: 99%